ANALYSIS OF TOTAL FLAVONOID LEVELS IN BROWN ALGAE (SARGASSUM SP. AND PADINA SP.) AS ANALGESIC DRUG THERAPY - M, Ruslin; Husain, Akbar Fuad; As, Hajrah Yusuf; Subehan, Subehan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Brown algae is one of the most interesting phyla that consist of pharmacologically active compounds and have been widely studied in recent years. One of the active compounds contained in brown algae that are known to have an analgesic effect is flavonoids. The aim of this study is to analyze the total amount of flavonoid compound in Sargassum sp. and Padina sp. as an analgesic drug. Methods: Samples used in this study were brown algae Sargassum sp. and Padina sp. taken from the Punaga Ocean, Takalar, South Sulawesi. The samples were extracted using the maceration method. After the extraction procedure, the total flavonoid levels were measured using a quercetin standard curve at maximum frequency. Results: Based on the measurement results, the total flavonoid levels in Sargassum sp. are 1.428%Â±sSD 0.168%. Conclusion: Padina sp. has higher total flavonoid levels compared to Sargassum sp. and can potentially act as an analgesic drug.